Current state and prospects for the legal regulation of cryptocurrencies in the European Union - Strilets, Bohdan (Actual problems of law (Aktual’ni problemi pravoznavstva), 2022)
The author analyzes the existing legal regulation of relations related to the use, issuance, trade and other operations with cryptocurrencies in the European Union law. It was noted that the development of cryptocurrency markets in the EU requires a well-built legal framework clearly defining the regulation regime for all cryptocurrencies that are not subject to current legislation on financial services. The main directions of regulatory influence on the cryptocurrency market in some EU Member States are identified. The problems of the system of legal acts covering legal relations with cryptocurrencies are analyzed. It was stated that creating a high-quality and effective legal framework within the EU internal market is an extremely important though challenging task. Perspective directions of legal regulation of crypto-assets according to the Proposal for a Regulation of the European Parliament and of the Council on Markets in Crypto-assets, and amending Directive (EU) 2019/1937, COM/2020/593 final, are analyzed. When analyzing the draft Regulation, it was found that its adoption would be an important step towards maximum harmonization of cryptocurrency legislation. A number of problems of the future legal act have been revealed. These include ambiguous legal regulation of cryptocurrency market participants’ cybersecurity. In addition, the legislative bodies should bear in mind that cryptocurrencies are in the process of constant transformation and transition from one type of token to another. In this case, the rules of the upcoming Regulation should be more flexible to future changes. It was concluded that according to the current draft Regulation, it is extremely unlikely that any types of crypto-assets will remain unregulated in the EU.